THE USE OF STORY MAP IN IMPROVING THE YEAR FOUR PUPILS’ ABILITY IN READING COMPREHENSION - Kee Li Li; Ngo Pei Wen (Journal of English Education, 2017)
This is an action research on improving reading comprehension through story map among Year 4 pupils in one of the primary schools in Malaysia. My pupils were unable to answer WH-questions of the narrative texts. The research aimed to use story map to improve pupils’ reading comprehension and improve my teaching practices in reading comprehension. I am the researcher with 24 pupils, 12 males and 12 females. I utilized three data collection methods: pre-reading comprehension test and post-reading comprehension test, pupils’ work and teacher’s reflective journal. I introduced story map through demonstration. Then the participants completed the story through literary elements identification based on the narrative texts. Findings showed that story map helped to improve pupils’ reading comprehension by identifying literary elements and relating the literary elements with the comprehension questions. The story map gave positive impact to reading comprehension. The research has impacted the teaching and learning environment, pupils’ learning, and my teaching practices. I found out that story map was a useful method in attracting pupils’ attention and teaching literary elements. Furthermore, I was developed to be a reflective teacher in terms of strengths and weaknesses of the teaching and learning process. Story map can be an effective tool in improving reading comprehension among pupils. In addition, a more interactive story map which incorporates Information and Communication Technology (ICT) may also be employed in further research.